HUBUNGAN MUTU PELAYANAN TERHADAP TINGKAT KEPUASAN PASIEN DI INSTALASI RAWAT JALAN RS SENTRA MEDIKA CIBINONG PADA ERA NEW NORMAL TAHUN 2021 - Izmi Azizah Zahra (2022)
One of the efforts in the health sector is the availability of good quality health services. Health services are a very essential type of community service, one indicator of the success of providing good quality health services can be seen from the level of patient satisfaction. This study aims to analyze the relationship between service quality (in terms of technical competence, access to services, effectiveness, efficiency, safety, and comfort) to the level of patient satisfaction at the Outpatient Installation of Sentra Medika Cibinong Hospital. This study uses a quantitative method with a cross sectional design. Samples were taken using accidental sampling technique of 100 respondents using a questionnaire as a research instrument. Analysis of research data using chi-square test. The results of this study indicate that there is a relationship between the dimensions of technical competence (ρ=0.001), dimensions of access to services (ρ=0.000), dimensions of effectiveness (ρ=0.000), dimensions of efficiency (ρ=0.000), dimensions of security (ρ=0.002) and the dimension of amenities (ρ=0.002) on the satisfaction level of outpatients. To Sentra Medika Cibinong Hospital, it is recommended to pay more attention to outpatient satisfaction by improving the quality of existing services in related dimensions.